Performance Evaluation and Future Prospects of Mutual Fund Industry in India - Pandey, Shyam Lal Dev; Rathore, Dr. G. S.; Khare, S. P. (Indian Journal of Finance, 2007)
There is a saying that "Money talks! But sadly, for most of us it talks only when it has to say "good-bye"! Here in reference to mutual funds money fails to say good-bye. The mutual funds were started with an aim to provide a platform for enabling the common man to invest in a professionally managed and risk diversified basket of securities at relatively low cost. The term "Mutual funds" describes a mechanism for pooling the resources by issuing units to the investors and investing funds in securities in accordance with objective as laid down in the offer document. Investing in basket of securities reduces the risk because all stocks may not move in the same direction in the same portion at the same time; therefore mutual funds are least risky avenue of investment. Mutual funds issue units to the investors in accordance with quantum of money invested by them. Investors of mutual funds are known as unit holders. The profit and losses are shared by investors in proportion to their investments. A mutual fund is required to be registered with Securities and Exchange Board of India (SEBI).